PENINGKATAN MOTORIK HALUS MELALUI PERMAINAN KOLASE KERTAS DI KELOMPOK A PADA TK DHARMA WANITA ILIR TALO KABUPATEN SELUMA PROPINSI BENGKULU - Haresmi Yuliana; Vivi Anggraini; Nur Hafiazah, Sahrul Ismet (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Fine motor skills are an important component of early childhood development that must be nurtured, as they contribute to a child’s readiness to advance to the next level of education. Observations in Group A at the Dharma Wanita Ilir Talo Kindergarten in Seluma Regency, Bengkulu Province, showed that some children still struggled with tasks requiring hand-eye coordination, such as cutting, pasting, and arranging materials. The study results indicated that paper collage activities can significantly improve children’s fine motor skills. In Cycle I, most children were still in the “Beginning to Develop” (MB) category, with average achievements that did not yet meet the success indicators. In Cycle II, the children’s fine motor skills improved, with 8% of children reaching the “Developing as Expected” (BSH) category and 73% reaching the “Developing Very Well” (BSB) category. Furthermore, under the initial conditions, paper collage activities can serve as an effective alternative learning medium to enhance the fine motor skills of early childhood students, as they foster creativity, concentration, independence, and enthusiasm for learning.